Lack of Galactose or Galacturonic Acid in Bradyrhizobium japonicum USDA 110 Exopolysaccharide Leads to Different Symbiotic Responses in Soybean - Quelas, Juan Ignacio (2010)
Exopolysaccharide (EPS) and lipopolysaccharide (LPS) from Bradyrhizobium japonicum are important for infection and nodulation of soybean (Glycine max), although their roles are not completely understood. To better understand this, we constructed mutants in B. japonicum USDA 110 impaired in galactose or galacturonic acid incorporation into the EPS without affecting the LPS. The derivative LP 3010 had a deletion of lspL-ugdH and produced EPS without galacturonic acid whereas LP 3013, with an insertion in exoB, produced EPS without galactose. In addition, the strain LP 3017, with both mutations, had EPS devoid of both galactosides. The missing galactosides were not replaced by other sugars. The defects in EPS had different consequences. LP 3010 formed biofilms and nodulated but was defective in competitiveness for nodulation; and, inside nodules, the peribacteroid membranes tended to fuse, leading to the merging of symbiosomes. Meanwhile, LP 3013 and LP 3017 were unable to form biofilms and produced empty pseudonodules but exoB suppressor mutants were obtained when LP 3013 plant inoculation was supplemented with wild-type EPS. Similar phenotypes were observed with all these mutants in G. soja. Therefore, the lack of each galactoside in the EPS has a different functional effect on the B. japonicum-soybean symbiosis.